Tingkat Kesegaran Jasmani Siswa SD di Kabupaten Demak - Mahardika, Galih Gilar; Rustiadi, Tri (Department of Physical Education, Sport, Health and Recreation, 2017)
The purposes of this study are (1) determine the physical fitness level of rural elementary students in Demak District Demak Regency, (2) determine the physical fitness level of urban elementary students in Demak District Demak Regency, (3) determine the physical fitness level that is better between elementary students in rural and urban areas in Demak District Demak Regency. The research subjects were the fifth grade elementary students in Demak District Demak Regency in 2016. The data collection used test survey technique and measurement. The results showed that rural elementary schools got a percentage of physical fitness level of 49.43% with the details for very less category were 2 students (5%), less category were 27 students (64%), medium category were 13 students (31%), good category was 0 student (0%) and very good category was 0 student (0%), whereas the urban elementary schools got a percentage of 41.63% with the details for very less category were 31 students (29%), less category were 71 students (66%), medium category were 6 students (5%), good category was 0 student (0%) and very good category was 0 student (0%). It can be concluded that the physical fitness level of elementary students in rural areas was better than those in urban areas in Demak District Demak Regency.